The Empirical Determinants of Aggregate Demand and its Effects on the Nigerian Population (Global Journal of Management and Business Research, 2017)
This study was carried out to examine the determinants of aggregate demand in Nigeria during the period 1970 to 2014. The paper traced the fiscal policy and noted in fiscal policy, the government uses taxation and its own expenditure factors of aggregate demand to steer up the economy in its desired direction. It was observed that the federal Government and the other tiers of government operated consisted huge deficit budgets for this period by relying on the two major factors. The objective of this study is to investigate and ascertain the determinants of aggregate demand in Nigeria between 1970 and 2014 given the argument that Government spending and not tax reduction that determines aggregate demand. The ultimate aim was to ensure adequate use of all factors responsible for stimulating the economy and increase aggregate demand. Our study in five segments, was an attempt at trying to know where Nigeria has been going wrong in her use or application of the Aggregate Demand stimulants to fine tune the economy. An Econometrical approach was adopted in analyzing the data collected. Ordinary least squares (OLS) and cointegration methods have been employed specified in a functional notation form relating Aggregate demand (AD) as dependant variables to seven (7) determinant stimulants.